2013
DOI: 10.1128/aac.02542-12
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nitazoxanide against Clinical Isolates of Mycobacterium tuberculosis

Abstract: c Nitazoxanide (NTZ) has bactericidal activity against the H37Rv laboratory strain of Mycobacterium tuberculosis with a MIC of 16 g/ml. However, its efficacy against clinical isolates of M. tuberculosis has not been determined. We found that NTZ's MIC against 50 clinical isolates ranged from 12 to 28 g/ml with a median of 16 g/ml and was unaffected by resistance to first-or second-line antituberculosis drugs or a diversity of spoligotypes.T reatment of drug-sensitive tuberculosis (TB) currently involves treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
(39 reference statements)
1
36
0
Order By: Relevance
“…Relative aqueous solubility did not appear to be a factor, as the partition coefficient (cLogP) of amixicile is 1.1, while VPC16a1011, which binds plasma at Ͼ99%, is insoluble in water (cLogP, 3.0). The latter result is similar to that reported for NTZ (cLogP, 2.2), which is 99% bound to plasma proteins (30,31), and it is known that high protein concentrations affect the potency of NTZ (MIC tests) against pathogens (33). We had previously reported that bovine serum albumin does not affect the MIC of amixicile (15).…”
Section: Drug Metabolismsupporting
confidence: 77%
“…Relative aqueous solubility did not appear to be a factor, as the partition coefficient (cLogP) of amixicile is 1.1, while VPC16a1011, which binds plasma at Ͼ99%, is insoluble in water (cLogP, 3.0). The latter result is similar to that reported for NTZ (cLogP, 2.2), which is 99% bound to plasma proteins (30,31), and it is known that high protein concentrations affect the potency of NTZ (MIC tests) against pathogens (33). We had previously reported that bovine serum albumin does not affect the MIC of amixicile (15).…”
Section: Drug Metabolismsupporting
confidence: 77%
“…4C). Similarly, nitazoxanide (NTZ), which is also active against both replicating and nonreplicating Mtb (34,35), exhibited dosedependent killing of starved Mtb up to 100 μM but left no significant DD Mtb population (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, SQ109 (2) has similar activity against both organisms (29), and with H. pylori, SQ109 (2) once again has a very low (≈10 −12 ) frequency of resistance (29). In addition, nitazoxanide (13) has been found to kill both replicating and nonreplicating M. tuberculosis (30)(31)(32)(33), and Nathan and coworkers (30,31) were unable to develop resistant colonies using up to 10 12 cfu, proposing a dual "PMF + unknown target" mechanism of action. Niclosamide (12) has been proposed as a lead for the treatment of type II diabetes (34), and it is also an inhibitor of breast cancer stem-like cells (35) and an inhibitor of Pseudomonas aeruginosa quorum sensing (36).…”
mentioning
confidence: 99%